Association between visceral and subcutaneous adiposity and clinicopathological outcomes in non-metastatic clear cell renal cell carcinoma - Mano, Roy; Hakimi, A Ari; Zabor, Emily C; Bury, Marta A; Donati, Olivio F; Karlo, Christoph A; Bazzi, Wassim M; Furberg, Helena; Russo, Paul (Canadian Urological Association Journal, 2014)
Introduction: Visceral adiposity has been inconsistently associated with clinicopathologic features and outcomes of clear cell renal cell carcinoma (ccRCC); however, most studies were conducted in non-Western populations. We evaluated the associations between visceral and subcutaneous adiposity and clinicopathological characteristics of non-metastatic ccRCC patients in a Western population. Methods: The medical records of 220 surgically treated ccRCC patients with documented preoperative body mass index (BMI) and computed tomography (CT) scans were retrospectively reviewed. Nineteen patients with stage IV disease were excluded. Visceral (VFA) and subcutaneous fat area (SFA) were computed from preoperative CT scans. Correlations between obesity measures were assessed with Pearson correlation. Associations between obesity measures and pathologic features were evaluated using logistic regression models adjusted for sex. Overall survival (OS) probabilities were estimated using Cox regression analysis. The log-rank test was used for group comparisons. Results: The study cohort comprised 150 men and 51 women. Women had higher SFA (p = 0.01) but lower VFA (p < 0.001) than men. BMI was highly correlated with SFA (r = 0.804) and moderately correlated with VFA (r = 0.542). SFA and VFA were weakly correlated (r = 0.367). An increased BMI was associated with a better OS (p = 0.028). When adjusting for sex, neither SFA nor VFA was significantly associated with tumour grade, stage, or OS. Conclusions: Consistent with prior reports, our study suggests that increased BMI is associated with a better OS for patient with non-metastatic ccRCC. Despite the high correlation between SFA and BMI, neither SFA nor VFA were significantly associated with tumour stage, grade, or OS in the current study; however, further studies in larger cohorts are required to validate this finding.